HRXRD and micro-CT multiscale investigation of stress and defects induced by a novel packaging design for MEMS sensors. (December 2022) - Borzì, Aurelio; Zboray, Robert; Dolabella, Simone; Brun, Sébastien; Telmont, Florian; Kupferschmied, Peter; Néal, Jean-François Le; Drljaca, Pedrag; Fiorucci, Gianni; Dommann, Alex; Neels, Antonia
Highlights: A unique, holistic X-ray analytical approach enables industrial implementation of MEMS microfab-rication novelty. Unrivaled strain evaluation by HRXRD reduces Si stress-detection threshold below 1 MPa. Impulse Current Bonding as a breakthrough in the field of MEMS packaging. Significant energy reduction of Impulse Current Bonding and increased applicability for materials joining. Sub-micron defects analysis in materials' bulk and bonding interfaces non-destructively by high-resolution X-ray micro-CT. Abstract: Advanced methods such as high-resolution X-ray diffraction and X-ray micro CT allow highly precise determination of materials' residual stress, volume, and lattice defects. Their conjoint exploitation offers a powering tool to facilitate the industrial implementation of novelties in microfabrication. The wafer-level packaging represents a critical step of the MEMS microfabrication resulting in a hermetic, defect- and stress-free interface. For the first time, such critical parameters are investigated related to a novel wafer-bonding process, namely Impulse Current Bonding (ICB), and compared to the standard anodic bonding technology used for MEMS production. The ICB does not induce any relevant residual stress at the interface above the limit of 1 MPa, determined by the unrivaled strain detectability of HRXRD. The bonding interface is devoid of any defects, as defined by X-ray micro-CT studies. The ICB technology reduces the thermal budget of the packaging up to 85% compared to the anodic bonding, which outlines an outstanding step forward in reducing the energy footprint. The extension of ICB to other materials systems such as glass to ceramic or metals makes this technology a promising candidate for numerous applications, including the design of biocompatible devices for bio-implants. Graphical_abstract: Image, graphical abstract